P2.112 The Enygma of Buschke-Löwenstein in the HPV Vaccine Era. (13th July 2013) - Skerlev, M; ele-Starčević, L; Ljubojevicć, S
Abstract : Background and open questions: Buschke-Löwenstein tumour (BLT) or giant condyloma acuminatum is a semimalignant neoplasm of the external genitalia and the perianal region. The hallmark of BLT is its possible transformation into squamous cell carcinoma (SCC) despite its histological benignity, and high rate of local recurrence. Most authors believe that BLT is a type of verrucous carcinoma (VC). Other authors suggested that BLT and VC are two distinct entities, in spite of all morphologic similarities, and the basic difference they investigate is correlation of BLT and HPV infection and p53 inactivation. It has been proposed that BLT represents intermediate state between CA and SCC. Malignant transformation to invasive SCC has been reported in 30–56% of cases. The variety of impressive clinical features in our patients with BLT, including the subjects in the age of 1.5 years support these findings. HPV DNA type 6 or 11 is regularly found in most (but not all) types of BLT, strongly suggesting its aetiological role in tumour development. In all of our BLT patients HPV DNA 6 has been revealed, except in 1 patient with HPV DNA 18. Accordingly, in this patient the histopathological evidence of malignancy (SCC) was documented! Due to lack of controlled studies about BLT, uniform treatment guidelines have not yet been established. Conclusion: An analysis of most published cases, including our own experience brought up conclusion that only consistently effective therapy is wide surgical excision of the tumour with clear margins, in spite of some anecdotal reports of the successful treatment with interferon or immiquimod. The recent introduction of a HPV vaccine (especially the quadrivalent one considering the prevention of the anogenital warts in men) has ushered in new hope of substantially reducing global prevalence of HPV disease and the burden of BLT.